SOLVING THE DEGREE CONSTRAINED MINIMUM SPANNING TREE PROBLEM USING TABU AND MODIFIED PENALTY SEARCH METHODS - Wamiliana Wamiliana (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2004)
In this paper we consider the Degree Constrained Minimum Spanning Tree Problem. This problem is concerned with finding, in a given edge weighted graph G (all weights are non-negative), the minimum weight spanning tree T satisfying specified degree restrictions on the vertices. This problem arises naturally in communication networks where the degree of a vertex represents the number of line interfaces available at a center. Because of its NP-completeness, a number of heuristics have been proposed. In this paper we propose two new search methods: one based on the method of Tabu search and the other based on a penalty function approach. For comparative analysis, we test our methods on some benchmark problems. The computational results support our methods.